A PDDL+ Benchmark Problem: The Batch Chemical Plant - Della Penna, Giuseppe; Intrigila, Benedetto; Magazzeni, Daniele; Mercorio, Fabio (Proceedings of the International Conference on Automated Planning and Scheduling, 2010)
The PDDL+ language has been mainly devised to allow modelling of real-world systems, with continuous, time-dependant dynamics. Several interesting case studies with these characteristics have been also proposed, to test the language expressiveness and the capabilities of the support tools. However, most of these case studies have not been completely developed so far. In this paper we focus on the batch chemical plant case study, a very complex hybrid system with nonlinear dynamics that could represent a challenging benchmark problem for planning techniques and tools. We present a complete PDDL+ model for such system, and show an example application where the UPMurphi universal planner is used to generate a set of production policies for the plant.